Integrating transcriptome and metabolomics revealed the key metabolic pathway response of Amaranthus retroflexus L. to the resistance to fomesafen. - Weifeng Song; Qinghui Wei; Zhenghao Shi; Yaqing Pan; Zhiyong Li; Fangyuan Wang (PLoS ONE)
Background Amaranthus retroflexus L. is one of the main broad-leaved weeds in soybean fields in Heilongjiang Province and is an important factor affecting soybean yield. It is becoming increasingly resistant to herbicides. However, studies on the transcriptome level and the molecular mechanism of secondary metabolite accumulation of resistant varieties of Amaranthus retroflexus L. have not been reported. Therefore, comprehensive analysis of transcriptome and metabolome is needed to determine the key metabolic pathways and key genes of Amaranthus retroflexus L. Results The biosynthetic pathway of resistance to Amaranthus retroflexus L. was studied by transcriptome and metabolome analysis. Transcriptome analysis showed that in the three comparison groups, compared with untreated (CK) group, there were 979 Differentially expressed genes (DEGs) in resistant (RY) group and 15731 DEGs in sensitive (SY) group; The RY group had 13822 DEGs compared to the SY group. Fluorescent quantitative PCR detection found that two gene tables related to Cytochrome P450 Monooxygenase (P450), Glutathione S-transferase (GST) and other enzyme systems such as peroxidase (POD), polyphenol oxidase (PPO), Catalase (CAT) and Superoxide dismutase (SOD) were significantly reached. Using Venn analysis for metabolomics analysis (VIP>1 and P<0.05), 239 Differentially expressed metabolites (DEMs) were selected. There are 15 common DEMs in the three control groups, and 8 unique DEMs in the RY group. This study detected 76 cases of DEMs and 139 cases of DEMs in the CK, RY, and SY control groups, respectively. More metabolites were detected in the CK and SY control groups. This viewpoint provides evidence for the genetic and metabolic differences between resistance and sensitivity in Amaranthus retroflexus L.. The KEGG in the RY vs SY group is mainly enriched in cysteine and methlonine metabololism, glycine, serine and threonine metabololism, aminoacyl-tRNA biosynthesis, biosynthesis of variant plant secondary metabololites, biosynthesis of amino acids, arginine and proline metabololism, biosynthesis of cofactors. Therefore, the resistance mechanism of Amaranthus retroflexus L. may be mainly generated by the metabolic pathway mechanism of amino acids. Conclusion In this study, DEGs and DEMs were identified by de novo Transcriptome assembly and metabonomic analysis, and an important metabolic pathway of resistance was found. It was found that the resistance mechanism of Amaranthus retroflexus L. might be mainly produced by amino acid metabolic pathway. This discovery laid the foundation for further research on the molecular mechanism and functional characteristics of the resistance of Amaranthus retroflexus L..